Further follow up of mortality in a United Kingdom oil distribution centre cohort. - Rushton, L (1993)
Results of an extension of follow up (1976 to 1989) of a cohort of workers employed for at least one year between 1 January 1950 and 31 December 1975 at oil distribution centres in Britain are presented. Over 99% of the workers were successfully traced to determine their vital status at 31 December 1989. The mortality observed was compared with that expected from the death rates of all the male population of England and Wales. The mortality from all causes of death for the total study population was less than that of the comparison population, and reduced mortality was also found for many of the major non-malignant causes of death. No healthy worker effect was found for ischaemic heart disease, and raised mortality from this disease was found in particular for one company and in several job groups. Raised mortality was also found for aortic aneurysm. Mortality from all neoplasms was lower than expected overall, largely due to a deficit of deaths from malignant neoplasm of the lung. Raised mortality patterns from all neoplasms, malignant neoplasm of the lung, and several non-malignant disease groups were found for general manual workers although the mortality from many of these diseases for all men in this social class in the national population is also high. There was increased mortality from malignant neoplasms of the larynx and prostate but these tended to be in isolated subgroups. Mortality from malignant neoplasm of the kidney was raised overall and in drivers in particular. Mortality from leukaemia was high at one company and in drivers overall.